A novel and practical asymmetric synthesis of eptazocine hydrobromide - Li, Ruipeng; Liu, Zhenren; Chen, Liang; Pan, Jing; Lin, Kuaile; Zhou, Weicheng (Beilstein Journal of Organic Chemistry, 2018)
In order to prepare eptazocine hydrobromide effectively, a novel, mild and practical asymmetric process was developed starting from 1-methyl-7-methoxy-2-tetralone under the catalysis of N-(p-trifluoromethylbenzyl)cinchonidinium bromide. The reaction conditions were optimized to obtain the product in excellent overall yield and purity.
Keywords: alkylation; asymmetric catalysis; eptazocine; Mannich cyclization